Governing New Guinea : an oral history of Papuan administrators, 1950-1990 - Visser, Leontine (Leiden : KITLV Press, 2012)
The book brings together 17 oral histories of the everyday life of Papuan civil servants.
Includes bibliographical references (page 347-351) and index.
Keywords: Indigenous peoples -- Papua New Guinea -- Politics and government; Civil service -- Papua New Guinea; Oral history -- Papua New Guinea; Papua New Guinea -- Politics and government